3D scanner application in the function of digital foot antropometry (FootSABA 3D Foot Scanner) - Baksa, Sarajko; Baksa, Ines; Mijović, Budimir, inženjer strojarstva (2019)
The personalization of footwear in terms of dimension and shape is of the utmost importance and is nowadays considered vitally important by interdisciplinary professions (medical, footwear, ergonomics ...), since inadequately manufactured footwear inevitably results in unwanted pathological conditions of the feet.The aim of this study is to scientifically determine the application of automated 3D digitization of spatial anthropometric foot measurement in relation to the frequency of incorrectly selected footwear based on traditional methods of measurement and selection.Among the examined individuals, both male and female, it was found that more than two thirds of people wear footwear that ergonomically does not fit the basic anthropometric footwear measurements, both in width and length of their feet.There is medical evidence that wearing inappropriate footwear is closely related to pain and wounds on the feet, and that prolonged wearing leads to pathological changes of the feet, such as foot and toe deformation.In the scope of taking measures, traditional methods of determining foot morphology are not sufficient to accurately define the shape and size, in contrast to the modern approach of using 3D scanners and digital methods of measuring virtual 3D models, which enable a very accurate and quick personalization of a large amount of anthropometric data concerning foot morphology.
Bibliografija: 11 jed.
Summary.
Keywords: Stopalo -- 3D virtualni model -- 3D skener -- Antropometrĳsko mjerenje